Unraveling the electrocatalytic reduction mechanism of enols on copper in aqueous media - Zhihao Cui; Xing’an Dong; Sung Gu Cho; Modeste N. Tegomoh; Weidong Dai; Fan Dong; Anne C. Co (Nature Communications, 2022)
Understanding the electrochemical deoxygenation pathway of aldehydes and ketones is important yet challenging. Here the authors use acetaldehyde as a model system to elucidate the role of enols in the electroreduction of aldehydes and ketones, which may shed light on the reaction pathway of CO2 to C2 and C3 products.